Analisis Mutu Sensorik dan Komposisi Kimia pada Cold Dessert dengan Penambahan Udang Vannamei (Litopeaneus vanname) - Luthfiah, Luthfiah; Rahmawati Saleh; Tasir, Tasir; Ernawati Jassin; Jihan Rasyieda (JURNAL RISET RUMPUN MATEMATIKA DAN ILMU PENGETAHUAN ALAM, 2025)
Dessert as a dessert, which is part of culinary in various cultures. Dessert is not only a dessert, but also reflects creativity and innovation in the culinary field. This study aims to analyze the comparative level of adding vannamei shrimp (Litopeaneus Vanname) to the cold dessert formulation on sensory properties (color, aroma, texture, and taste) and chemical composition (protein content and fat content). The study was conducted experimentally using a Completely Randomized Design (CRD) with three treatments of adding vannamei shrimp, namely 10% (A1), 20% (A2), and 30% (A3). The results of the organoleptic test showed that treatment A1 (10% shrimp addition) gave the best value on all sensory parameters, with an aroma value of 4.3 (like), taste 4.7 (like), texture 4.2 (like), and color 4.2 (like). Chemical analysis showed that treatment A1 produced a protein content of 4.21% and a fat content of 8.46%. The addition of vannamei shrimp to the cold dessert formulation is an attractive taste innovation for consumers. This study concludes that the addition of vannamei shrimp to cold dessert formulations can be an attractive alternative to improve the quality and nutritional value of products, as well as meet the growing needs of consumers.